Morphology of the first and second instars larvae of Peckia (Peckia) chrysostoma (Wiedemann, 1830) (Diptera, Sarcophagidae). - Buenaventura, Eliana (Instituto de Ecología, A.C., 2013)
The morphology of larval stages of Diptera (Insecta) is little known, especially in the case of Sarcophagidae family larvae. Interest in sarcophagid larvae studies has increased with the step forward of forensic entomology, where they are considered potential indicators of the time of death. Forensic studies show Peckia (Peckia) chrysostoma as one of the most important species in the Neotropical region. However, taxonomic identification of larvae is difficult due to the lack of knowledge of its morphology and useful taxonomic characters for identify them. Sealed microscope slides of first and second instar larvae were performed. The pseudocephalon, cephalopharyngeal skeleton, spinules, spiracular atrium and the posterior spiracles were studied. Morphological characteristics of larval instars I and II were described and illustrated.